Profiling of Physical and Chemical Properties of Mango at Different Ripening Stages - Islam, MS; Aziz, MG; Mortuza, MG; Rahman, MA (Journal of Environmental Science and Natural Resources, 2017)
The experiments were carried out to assess the quality of mango at different ripening stages. The two factor experiment was laid out in completely randomized design (CRD) with three replications. The experiment comprised four varieties, viz., V1: BAU Aam-1, V2: BAU Aam-6, V3: BAU Aam-7, V4: BAU Aam-8 and five ripening stages. Among the attributes total weight loss, dry matter content, total soluble solids (TSS), sugar content (total, reducing and non-reducing), disease incidence increased, while the moisture, vitamin C contents and titratable acidity decreased with the increase in duration of storage. Among the four varieties, BAU Aam-6 showed better results in relation to the most of the characters examined. Ripening stage-5 of mango fruit was observed to be the best among the five ripening stages in relation to the most of the chemical characters examined. Finally, it can be concluded that the results of this experiment will be useful with particular reference to quality control, preparation for transportation and marketing, and will also be beneficial for both the growers and consumers. J. Environ. Sci. & Natural Resources, 9(2): 121-126 2016